Ujaran Kebencian di Era Digital dan Kontekstualisasi Kalimah Thayyibah QS. Ibrahim [24] dalam Mewujudkan Kesolehan Sosial - Anggi, Muhammad; Sovia Lola; Najwa Syifa Nabila (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
This article discusses the negative impact of hate speech on social media and efforts to combat it by utilizing the concept of kalimah thayyibah in the Qur'an. The digital age has brought about a revolution in human communication, but it has also brought about negative impacts, including hate speech. Hate speech can damage social relations, and can even disturb the peace of society and trigger conflict. The Qur'an opposes hate speech and encourages good speech. The concept of kalimah thayyibah in the Qur'an, especially in Qs. Ibrahim verse 24, is explained as a good sentence like a sturdy tree. The research method used is a qualitative data collection technique method. This article also provides solutions to combat hate speech, including the roles of individuals, families, communities, media, and government. By applying kalimah thayyibah and cooperation from various parties, it is hoped that hate speech can be minimized on social media.